Mechanical and dielectric properties of epoxy/dicyclopentadiene bisphenol cyanate ester/glass fabric composites (eXPRESS Polymer Letters, 2008)
The impact and flexural strengths of epoxy-dicyclopentadiene bisphenol cyanate ester (EP-DCPDCE) hybrid thermoset as well as the interlaminar shear strength (ILSS) and flexural strength of the composites consisting of the hybrid thermoset and glass fabric were studied. It is found that the addition of epoxy resin (EP-51) can improve the mechanical properties, particularly, the impact strength of DCPDCE matrix and the ILSS of glass fabric reinforced composites. The improvements of the mechanical properties were obvious when the content of EP-51 is from 15 to 30 wt%. The investigations of the interphase of composites by scanning electron microscope (SEM) and dynamic mechanical analysis (DMA) confirm the improvement of mechanical properties of the composites. However the addition of EP-51 has negative effects on the thermal and dielectric property of the composites.